Menelusuri Dua Poros Pendidikan Islam: Studi Komparatif Sistem Pendidikan Arab Saudi dan Indonesia - Anisa Rahmatul Meiril; Suci Fadhilah Masja; Alya Nur Annisha; Aprizal Ahmad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to analyze and compare the education systems in Saudi Arabia and Indonesia through a literature study approach. This study highlights similarities and differences in educational objectives, curriculum structure, education management, and the types and levels of education applied in the two countries. In addition, this article reviews the history of the development of education in Saudi Arabia, especially the central role of Islamic education in shaping national education orientation and policy. The analysis shows that Saudi Arabia has an education system that is heavily influenced by religious values and Islamic law, while Indonesia develops an education system based on Pancasila with a more pluralistic approach. However, both countries face similar challenges, such as improving the quality of teachers, equitable access to education, modernizing the curriculum, and adapting to technological developments and globalization. The findings of this study confirm that despite fundamental differences in educational ideologies and approaches, Saudi Arabia and Indonesia share a common commitment to improving the quality of human resources through strengthening the national education system. This article is expected to serve as a reference for comparative research on education in Muslim-majority countries.